Finite Element Analysis on the Creep Constitutive Equation of High Modulus Asphalt Concrete - Xiu-shan Wang; Tao-tao Fan; Lum Kitmeng (Advances in Materials Science and Engineering)
In order to obtain the viscoelastic constitutive relation of High Modulus Asphalt Concrete (HMAC), the constitutive relationship is used to carry on the various numerical calculation, utilize integral transforming in its Bailey-Norton creep rule, and establish new practical model. Combining with the collection data from creep tests of uniaxial compression, regression calculation is carried out with 1STOPT fitting software; thus the creep parameters of High Modulus Asphalt Concrete in different temperatures were obtained, which can be used in HMAC creep model.